Integrating groundwater recharge solutions across the Ramganga Basin, India: a rural-urban approach - Angou, G.; Alam, Mohammad Faiz; Sharma, Navneet; Pavelic, Paul; Sikka, Alok (International Water Management Institute, 2024)
A study carried out by IWMI, TU Delft and Wageningen University looked at how groundwater recharge can help meet growing demands in both rural and urban parts of the Ramganga Basin, India.